Project-Based Learning: An Innovative Learning Model to Improve the Understanding of Science in Fifth-Grade Students - Asprila, Fiskawati Derate; Subiyantoro, Singgih (Cognitive Development Journal, 2024)
The lack of understanding of elementary school students in the subject of science, especially the material on the human digestive system, is the background of this study. The purpose of this study is to improve the understanding of fifth-grade students on the material on the human digestive system by using the Project-Based Learning (PjBL) learning model. The method used in this study is classroom action research consisting of 2 cycles with four stages, namely planning, action, observation and reflection. The data analysis techniques used in this study are participatory observation techniques, data utilization techniques and document data analysis. The subjects of the study were 15 fifth-grade students. The results of the study showed that students' understanding increased after the PjBL model was applied, as evidenced by the percentage of students' average scores in the pre-cycle not reaching the criteria for achieving learning objectives; then in cycle I, the score increased by 13% and in cycle II it increased by 20%. This research is expected to contribute to educational institutions to provide information in improving the quality of education.